Hispatologi Jantung Tikus pada Toksisitas Sub Kronis Ekstrak Etanol 70% Kulit Buah Jeruk Citrus nobilis Lour. - Izazi, Farizah; Prayogo, Bambang; Hestianah, Eka Pramyrtha; Zulkarnain, Endri (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2020)
This research aimed to study the histopathological heart rat of sub chronic toxicity 70% ethanol extract Citrus nobilis Lourr. Peel. This study used 40 male white Galur Wistar rats in sub-chronic toxicity and each divided into 4 groups (control group giving CMC Na 0,5%, dose group 40 mg/kg BB, dose group 200 mg/kg BB, and dose group 1000 mg/kb BB). Each group consists of 10 males. Each cage contains 5 rats of the same age and gender, fed and drunk in ad libitum method. Furthermore, the rats are being weighing in. 70% extraction of Citrus nobilis Lour peel is orally given to the rats, every day for 90 days accordance with the group. After rats were given dose treatment for 90 days then observed histopathology of heart. Each rat organ preparation was observed in five different fields of view then scored and processed with rank ratings then analyzed using non parametric statistical test using Kruskal Wallis test. 70% extraction of Citrus nobilis Lour peel for 90 days with a dose of 1000mg / kg of rats based on statistical tests showed damaged heart muscle cell on histopathological observation of the heart. It is then expected to continue on the chronic toxicity test of 70% extraction of Citrus nobilis Lour peel for 12 months to predict the safety of clinical use in humans in the long term. Key word: heart, Citrus nobilis Lour.of peel, sub chronic toxicity